The Soviet art of war : doctrine, strategy, and tactics - Scott, Harriet Fast; Scott, William Fontaine, 1919- (Routledge, 2019)
No other nation has invested as much intellectual capital in the study of war as has the Soviet Union over the last six decades, and the doctrine, strategy, and tactics that have been developed by Soviet theoreticians are bound to guide any future Soviet military action. The Soviet Art of War makes available to Western readers selections from the most significant and influential Soviet military writings from 1917 to the present. The Scotts have examined thousands of Soviet military publications, including the restricted journal of the Soviet General Staff, Voyennaya Mysl', to make this book the most comprehensive account of Soviet military theory and practice yet published. The papers they have chosen thoroughly illustrate the development of the basic features of Soviet military art, from the days of trench warfare to the era of the nuclear battlefield. These documents demonstrate the emphasis on surprise, on deception, on mass deep penetration of enemy defenses, and on a unified strategy for all services. They also show the forms of military action--destruction and attrition, defense and offense, maneuver and position-as seen through the eyes of leading Soviet marshals, generals, and admirals. The usefulness of this material is further enhanced by the Scotts' commentary and their analysis of each group of readings.